PSYCHOVEGETATIVE SYNDROME AS A CLINICAL MANIFESTATION OF ADAPTATION DISORDERS IN SENIOR MEDICAL STUDENTS - Mariana Kutura; Valeriy Levchenko (Eastern Ukrainian Medical Journal, 2022)
The objective of the paper was the verification of psychosomatic disorders against the background of disadaptation among senior medical students. Materials and Methods. We used screening and psychometric diagnostic methods to examine 292 4th-year students, 181 (62 %) of whom showed signs of disorders relating to psychological and emotional adjustment to the stressful influence of external irritants against the background of somatic symptoms. We used the standardized Spielberger–Hanin, Zung, Cohen, and Nijmegen questionnaires and anamnestic data for the in-depth questionnaire in our research. Results. When assessing the overall results of the psychometric screening, we found that more than half of the 4th-year students surveyed (62 %) had some signs of adjustment disorders. According to the Spielberger questionnaire, 43.65 % of students in the main group (n = 181) showed signs of increased state anxiety. The majority of young people showed signs of trait anxiety, among whom 53.04 % had severe anxiety disorders and 41.99 % had moderate anxiety disorders. According to the Zung questionnaire, 17 people showed signs of depression. The Cophen scale assessment revealed a high number of young people with low stress tolerance among respondents. We found that among 181 students, 35.36 % had a satisfactory result (6.8 ± 1.43 units) and 50.28 % had a poor result (28.2 ± 1.18 units). The remaining 10 students in this group had a very poor result (36.5 ± 2.16 units). 48 students in the main group showed positive results according to the Nijmegen questionnaire. On the background of the detected changes, psychosomatic symptoms were established in most students, which can act as a marker of a non-adaptive type of autonomic reaction. Conclusions. Screening assessment of medical students with the use of standardized questionnaires makes it possible to detect manifestations of psychovegetative dysfunction, disadaptation syndrome against the background of psychosomatic symptoms.